A road through the Mora forest Trinidad - A 10. - (:unkn) unknown (My University, 2010)
Back of postcard notes: "Mora forests are a striking feature of certain parts of Trinidad and an exception to the rule that tropical forests are an indiscriminate mixture of numerous trees. The labourers’ dwellings shown, are constructed of earth on a wooden framework and thatched with palm leaves."
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Villages--Trinidad and Tobago; Working class--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Forests and forestry--Trinidad and Tobago; Trees--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; [1910]; Huts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Children--Trinidad and Tobago; Hats--Trinidad and Tobago; Roads--Trinidad and Tobago